Language analysis of the promotional discourse of the halal food industry - Wan Nor Fasihah Wan Mohd Fadzlullah (Abdul Hamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
As the leading global halal hub, Malaysia has dominated the Global Islamic Economic Indicator for the eighth year in a row (DinarStandard, 2019). This achievement is contributed by the nation’s biggest source of halal export, which are halal food and beverages that is estimated to be worth RM 22 million in 2019 (Halal Development Corporation, 2020). To further strengthen Malaysia’s halal sphere, the Halal Industry Master Plan 2030 (Halal Development Corporation, 2018) has proposed an objective to resolve current issues in the halal industry, which includes mislabeling and ambiguous advertising. This study aims to tackle these linguistic based issues through identifying the language mechanics used in the halal food promotional discourse and determining the role of these linguistic elements in delivering the halal message. Two hundred halal food promotional materials were collected from several halal exhibitions in Klang Valley and resulted in a 19,742 word halal promotional corpus. Through discourse analysis, the identification of rhetorical devices were supported with the Framework of Rhetorical Devices by Zulkipli and Ariffin (2019) and the intertextuality and interdiscursivity were analyzed through multi perspective discourse analysis (Bhatia, 2002). The Framework of Islamic Advertising (Mokhtar, 2016) was also employed to map the linguistic elements following Maqasid Shariah’s principle of protecting the religion. This study uncovered the fact that although halal rhetorics were not fully utilized by all halal brands, elements of advertising mildly and truthfully were the highest among other Islamic elements as evident in the usage of modest language and displaying halal logos. The findings were consistent with the feedback from halal food companies which emphasized that they focused their halal marketing strategy mainly through displaying halal logo because it was deemed enough to represent the halal message in the halal food promotional discourse.